A review of the most important natural antioxidants and effective medicinal plants in traditional medicine on prostate cancer and its disorders - Gholam Basati; Pardis Ghanadi; Saber Abbaszadeh (Shahrekord University of Medical Sciences, 2020)
Herbal plants can be used to treat and prevent life-threatening diseases, such as prostate cancer, infections and other diseases. The findings from traditional medicine and the use of medicinal plants can help control and treat most problems due to prostate diseases. The aim of this study was to identify and report the most important medicinal plants that affect prostate disorders. Based on the results of the review of numerous articles indexed in the databases ISI, Scopus, PubMed, Google Scholar, etc., a number of plants have been reported to be used in the treatment and prevention of diseases, inflammation, infection, and cancer of the prostate gland. The plants include Panax ginseng, Arum palaestinum, Melissa officinalis, Syzygium paniculatum, Coptis chinensis, Embelia ribes, Scutellaria baicalensis, Tripterygium wilfordii, Salvia triloba, Ocimum tenuiflorum, Psidium guajava, Ganoderma lucidum, Litchi chinensis, Saussurea costus, Andrographis paniculata, Magnolia officinalis and Prunus africana. Phytochemical investigations have examined the therapeutic effects of medicinal plants effective on prostate cancer and their possible mechanisms of action and clinical effects as well as the use of active flavonoids in production of herbal drugs. Due to the active ingredients and important flavonoids of these plants, they can be used in production of herbal drugs that prevent and treat infections, inflammation and cancer of the prostate gland, and reduce the metastasis of prostate cancer cells, reducing the patients' suffering and pain.